On Common Ground - Burton L. Edefstein, DDS, MPH (Blackwell Synergy)
Ladies and gentlemen, friends and colleagues, and collaborators-more precisely ÃƒÂ¢Ã¢â€šÂ¬Ã‚Âco-laborersÃƒÂ¢Ã¢â€šÂ¬Ã‚Â in the endeavor to improve the oral health of the American public-good morning and good wishes as you inaugurate your first joint meeting of ASTDD and AAPHD and bring into your midst the ADA, AAPD, ADEA, Medicaid dental program directors, ADHA, and so many others. How refreshing it is to officially recognize an activity that codifies something each of you already knows-that coalition building begins at home and that we are us.